The Richard and Hinda Rosenthal Lecture 2007: Transforming Today's Health Care Workforce to Meet Tomorrow's Demands - Institute of Medicine; Institute of Medicine (The National Academies Press, 2008)
In 1988, a new outreach program was launched at the Institute of Medicine. Through the generosity of the Richard and Hinda Rosenthal Foundation, a lecture series was established to bring to greater attention some of the critical health policy issues facing our nation today. Each year one or more experts present their views and insights on a major health topic, and the Institute of Medicine later publishes these lectures for the benefit of a wider audience. The Rosenthal Lectures have attracted an enthusiastic following among health policy researchers and decision makers in Washington, D.C., and across the country. The lectures typically engender a lively and productive dialogue. In this volume, we are proud to present the remarks of the 2007 Rosenthal Lecturers—Drs. Kevin Grumbach, Fitzhugh Mullan, and Marla E. Salmon—who spoke on "Transforming Today's Health Workforce to Meet Tomorrow's Demands."
Keywords: Health and Medicine

Space Science and the International Traffic in Arms Regulations: Summary of a Workshop - National Research Council (The National Academies Press, 2008)
ITAR, which controls defense trade, includes the U.S. Munitions List (USML) which specifies categories of defense articles and services covered by the regulations. In 1999, space satellites were added to the USML. In 2002 ITAR was amended to exclude U.S. universities from having to obtain ITAR licenses when performing fundamental research involving foreign countries and/or persons. Despite this provision, there remains considerable uncertainty among university researchers about whether the regulations apply to their research leading to a rather conservative interpretation of the regulations and the imposition of burdens that might not be necessary. To explore this concern, NASA asked the NRC to organize a workshop of all stakeholders on the implications of ITAR for space science. This book presents a summary of the workshop discussions including those on perspectives on recent developments and implementation of ITAR; overarching issues; problems arising from ITAR's implementation; and opportunities for near-term actions and improvements.
Keywords: Conflict and Security Issues; Space and Aeronautics

Standardizing Medication Labels: Confusing Patients Less: Workshop Summary - Institute of Medicine (The National Academies Press, 2008)
Medications are an important component of health care, but each year their misuse results in over a million adverse drug events that lead to office and emergency room visits as well as hospitalizations and, in some cases, death. As a patient's most tangible source of information about what drug has been prescribed and how that drug is to be taken, the label on a container of prescription medication is a crucial line of defense against such medication safety problems, yet almost half of all patients misunderstand label instructions about how to take their medicines. Standardizing Medication Labels: Confusing Patients Less is the summary of a workshop, held in Washington, D.C. on October 12, 2007, that was organized to examine what is known about how medication container labeling affects patient safety and to discuss approaches to addressing identified problems.
Keywords: Health and Medicine

A Guide for Addressing Collisions Involving Motorcycles - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2008)
TRB's National Cooperative Highway Research Program (NCHRP) Report 500, Vol. 22: Guidance for Implementation of the AASHTO Strategic Highway Safety Plan: A Guide for Addressing Collisions Involving Motorcycles provides guidance on strategies that can be employed to reduce crashes involving motorcycles.In 1998, the American Association of State Highway and Transportation Officials (AASHTO) approved its Strategic Highway Safety Plan, which was developed by the AASHTO Standing Committee for Highway Traffic Safety with the assistance of the Federal Highway Administration, the National Highway Traffic Safety Administration, and the Transportation Research Board Committee on Transportation Safety Management. The plan includes strategies in 22 key emphasis areas that affect highway safety. The plan's goal is to reduce the annual number of highway deaths by 5,000 to 7,000. Each of the 22 emphasis areas includes strategies and an outline of what is needed to implement each strategy.Over the last few years the National Cooperative Highway Research Program (NCHRP) has been developing a series of guides, several of which are already available, to assist state and local agencies in reducing injuries and fatalities in targeted areas. The guides correspond to the emphasis areas outlined in the AASHTO Strategic Highway Safety Plan. Each guide includes a brief introduction, a general description of the problem, the strategies/countermeasures to address the problem, and a model implementation process.
Keywords: Transportation and Infrastructure

U.S. Conventional Prompt Global Strike: Issues for 2008 and Beyond - National Research Council (The National Academies Press, 2008)
Conventional prompt global strike (CPGS) is a military option under consideration by the U.S. Department of Defense. This book, the final report from the National Research Council’s Committee on Conventional Prompt Global Strike Capability, analyzes proposed CPGS systems and evaluates the potential role CPGS could play in U.S. defense. U.S. Conventional Prompt Global Strike provides near-, mid-, and long-term recommendations for possible CPGS development, addressing the following questions: Does the United States need CPGS capabilities? What are the alternative CPGS systems, and how effective are they likely to be if proposed capabilities are achieved? What would be the implications of alternative CPGS systems for stability, doctrine, decision making, and operations? What nuclear ambiguity concerns arise from CPGS, and how might they be mitigated? What arms control issues arise with CPGS systems, and how might they be resolved? Should the United States proceed with research, development, testing, and evaluation (RDT&E) of the Conventional Trident Modification (CTM) program5 and, ultimately, with CTM production and deployment? Should the United States proceed with the development and testing of alternative CPGS systems beyond CTM?
Keywords: Conflict and Security Issues

Toward a Transformational Africa-U.S. STEM University Initiative: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
STEM (science, technology, engineering, and mathematics) plays a key role in accelerating economic growth and developing innovative solutions to pressing challenges facing the African continent. Over the past few decades, much work has been done to develop university systems in African countries in recognition of the role that high-caliber teaching and research in STEM fields play in economic development. African universities and their governments have made many of these gains through partnering across countries and sectors. Often, however, these efforts are based on individual connections and do not lead to long-term change. Inspired by STEM's potential to tackle African and global challenges, a group of academic leaders has come together to explore a synergistic approach to transform African institutions of higher education and increase the global engagement of U.S. institutions. They developed an initial vision for a next-generation Africa-U.S. STEM initiative that would take place for at least 10 years, with funds of at least $10 million annually from governments, the private sector, philanthropies, and other organizations. To obtain input from stakeholders on how such an initiative could develop, the group held a virtual workshop March 14-16, 2022, convened by the National Academies of Sciences, Engineering, and Medicine. This publication summarizes the presentations and discussions of the workshop.
Keywords: Education

Emergency Response: Organizational and Operational Models Used by State DOTs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Large-scale emergencies and disasters (weather-related and other) may be somewhat rare but are not as rare as they used to be, and are generally increasing in intensity and frequency. How state departments of transportation (DOTs) train and coordinate prior to emergencies makes a big difference in how effectively they respond to an emergency. NCHRP Web-Only Document 378: Emergency Response: Organizational and Operational Models Used by State DOTs, from the TRB National Cooperative Highway Research Program, is designed to help transportation agencies improve their emergency response and support robustness and resilience into their operations. The document is supplemental to NCHRP Research Report 1088: State DOT Models for Organizing and Operating Emergency Response: A Guide.
Keywords: Transportation and Infrastructure

Forum on Microbial Threats: Annual Report 2022 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Since its establishment in 1996, the Forum on Microbial Threat has provided a platform for leaders from a wide range of disciplines and industries to debate and collaborate on the most effective ways to understand, anticipate, and manage emerging infectious diseases. The world still grapples with the COVID-19 pandemic at the same time as it addresses other infectious disease threats from mpox to highly pathogenic avian influenza and the spread of drug-resistant bacterial and fungal pathogens. In 2022, the forum held two workshops on antimicrobial resistant fungal pathogens and lessons learned from biomedical research and development during the COVID-19 pandemic. The forum also continued to work closely with the One Health Action Collaborative and remained committed to both cross-disciplinary and community public health discourse.
Keywords: Health and Medicine

Contrast Pavement Markings Practices (The National Academies Press, 2023)
Contrast pavement markings (CPM) improve the visibility of pavement markings by providing better contrast with the pavement surface, especially on lighter-colored pavements. NCHRP Synthesis 613: Contrast Pavement Markings Practices, from TRB's National Cooperative Highway Research Program, documents current CPM practice by state departments of transportation.
Keywords: Transportation and Infrastructure

Going Beyond BMI: Communicating About Body Weight: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The National Academies Roundtable on Obesity Solutions hosted "Going Beyond BMI: Communicating About Body Weight," the second workshop in the 2-part series "Exploring the Science on Measures of Body Composition, Body Fat Distribution, and Obesity," to explore communications strategies and solutions to improve messaging around obesity and adiposity. Speakers highlighted approaches to communicating the definitions and diagnoses of obesity, addressed weight bias and stigma, and discussed the challenges in cultural perceptions. Sessions focused on ways to mitigate misinformation and for providers to shift to a health-centric approach in obesity treatment. This proceedings document summarizes workshop discussions.
Keywords: Food and Nutrition

Bonded Concrete Overlays on Asphalt Pavements: Resources for Evaluation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The TRB National Cooperative Highway Research Program's NCHRP Web-Only Document 329: Bonded Concrete Overlays on Asphalt Pavements: Resources for Evaluation provides Appendices A through G of the contractor’s final report, which detail survey responses from transportation agencies on bonded concrete overlays on asphalt pavements as well as agency plans and projects. The document is supplemental to NCHRP Research Report 1007: Evaluation of Bonded Concrete Overlays on Asphalt Pavements.
Keywords: Transportation and Infrastructure

The Gates Are Open: Control System Cyber-Physical Security for Facilities: Proceedings of a Federal Facilities Council Workshop—in Brief - Linda Casola (The National Academies Press, 2021)
The expanding connectivity of operational technologies (OT) increases the vulnerability of facilities to cyber attacks. Many of these technologies were not designed for a "smart" environment and are thus unsecure. Furthermore, these devices often continue to be overlooked when considering overall building security, which can lead to significant losses. On August 10, 2021, the National Academies of Sciences, Engineering, and Medicine's Federal Facilities Council convened a virtual workshop to discuss OT security within facilities. Workshop panelists and participants explored existing vulnerabilities, new legislation and guidance, the convergence of cyber and physical security, and strategies to mitigate risk. This publication summarizes the presentation and discussion of the workshop.
Keywords: Computers and Information Technology

Airport-Centric Advanced Air Mobility Market Study - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Advanced air mobility (AAM) is a broad concept enabled by new technology with the potential to transform aviation and urban transportation systems over the next 10 years. Some of these technologies include electric vertical takeoff and landing (eVTOL) aircraft as well as traditional fixed-wing aircraft using electric or other advanced propulsion systems. ACRP Synthesis 130: Airport-Centric Advanced Air Mobility Market Study, from TRB's Airport Cooperative Research Program, is designed to help airports and other stakeholders as they plan for AAM. Many of the initial use cases for AAM will be integrated into existing airports of all sizes, including airport ground access, connecting passenger service between regional and hub airports, and cargo operations.
Keywords: Transportation and Infrastructure

Forum on Drug Discovery, Development, and Translation: 2023 Annual Review - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
In 2023, the Forum on Drug Discovery, Development, and Translation focused on diverse topics, including approaches to define and evaluate in-home drug disposal systems for opioid analgesics, the diagnosis and treatment of adults with attention-deficit/hyperactivity disorder and implications for drug development, strategies to optimize public–private partnerships for clinical cancer research, opportunities to prepare the future workforce in research and development, and other policy updates relevant to drug discovery, development, and translation. Learn more in this 2023 Annual Review.
Keywords: Health and Medicine

Targeting Structures, Communications, and Beliefs to Advance Practical Strategies for Obesity Solutions: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Keywords: Food and Nutrition

Use of Meta-Analyses in Nutrition Research and Policy: Interpretation and Application of Meta-Analysis to Evaluate the Totality of Evidence: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The third workshop in the series on the use of meta-analysis in nutrition research and policy, held on October 3, 2023, focused on the process for evaluating the strength of the totality of evidence for diet and health relationships, with consideration of the type of study designs (observational and interventions) and risk of bias. The workshop series concluded with a discussion of the different applications of meta-analysis to inform policy and guidance.
Keywords: Food and Nutrition

Safety at Midblock Pedestrian Signals - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Midblock pedestrian signals (MPSs) provide safety benefits and support “complete streets,” a transportation policy and design approach that calls for roadways to be designed and operated with all users in mind: bicyclists, public transportation users, drivers, and pedestrians of all ages and abilities.The TRB National Cooperative Highway Research Program's NCHRP Research Report 1030: Safety at Midblock Pedestrian Signals presents a state-of-the-practice guide to midblock pedestrian crossing treatments, summarizes the safety effectiveness of MPS installations, and proposes language for consideration in future updates to the Manual on Uniform Traffic Control Devices (MUTCD) for MPSs.Supplemental to the report is a Memo on Implementation of the Research Findings. A PDF file with alt text descriptions for the graphics is available upon request from Customer_Service@nap.edu.
Keywords: Transportation and Infrastructure

Developing an Emergency Response Playbook for State Transportation Agencies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Transportation plays a crucial role before, during and after an emergency. Transportation agencies’ unique role stems from their broad range of capabilities and responsibilities. NCHRP Web-Only Document 384: Developing an Emergency Management Playbook for State Transportation Agencies, from TRB’s National Cooperative Highway Research Program, helps develop a playbook to support emergency management program review and development for state transportation agencies.The document is supplemental to NCHRP Research Report 1093: An Emergency Management Playbook for State Transportation Agencies.
Keywords: Transportation and Infrastructure

The Roles of Trust and Health Literacy in Achieving Health Equity: Community Settings: Proceedings of a Workshop-in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The National Academies Roundtable on Health Literacy convened the third of three workshops to address the themes of trust and positive health equity outcomes that arise from strategic community-based organization practices. Given the historical and current reasons individuals and communities with marginalized identities have to mistrust public health communications and institutions, health literacy is essential. To bolster mutual trust, hospitals, payers, providers, and public health professionals should have the cultural competence and humility to match the health literacy needed from their patients.This Proceedings document summarizes workshop discussions.
Keywords: Health and Medicine

Report of the Committee on Proposal Evaluation for Allocation of Supercomputing Time for the Study of Molecular Dynamics: Thirteenth Round - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
This report evaluates submissions received in response to a Request for Proposals for Biomolecular Simulation Time on Anton 2, a supercomputer designed and built by D.E. Shaw Research (DESRES). Over the past 12 years, DERES has made an Anton or Anton 2 system housed at the Pittsburgh Supercomputing Center available to the non-commercial research community, based on the advice of previous committees of the National Academies of Sciences, Engineering, and Medicine. As in those prior rounds, the goal of the thirteenth Request for Proposals for simulation time on Anton 2 is to continue to facilitate breakthrough research in the study of biomolecular systems by providing a massively parallel system specially designed for molecular dynamics simulations. These capabilities allow multi-microsecond simulation timescales. The program seeks to continue to support research that addresses important and high impact questions demonstrating a clear need for the special capabilities of the Anton.
Keywords: Math, Chemistry, and Physics